Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Tìm x :
\(5x+x=39-3^{11}:3^9\)
\(6x=39-3^2\)
\(6x=39-9\)
\(6x=30\)
\(x=30:6\)
\(x=5\)
Thực hiện phép tính :
\(225:3^2+4^3.125-125:5^2\)
\(=225:9+64.125-125:25\)
\(=25+8000-5\)
\(=8020\)
a, 6x=39-3^2 b,225:9+64.125-125:25
6x=39-9 =25+64.125-125:25
6x=30 =25+8000-125:25
x=30:6 =25+8000-5
x=5 =8020
\(\left(x+15\right)-125=5^7:5^5\)
\(\Rightarrow\left(x+15\right)-125=5^2\)
\(\Rightarrow\left(x+15\right)-125=25\)
\(\Rightarrow x+15=25+125\)
=> x+15=150
=> x=150-15
Vậy x=135.
\(720:\left[41-\left(2x-5\right)\right]=2^3.5\)
=> 720:[41-(2x-5)]=8.5
=> 720:[41-(2x-5)]=40
=> 41-(2x-5)=720:40
=> 41-(2x-5)=18
=> 2x-5=41-18
=> 2x-5=23
=> 2x=23+5
=> 2x=28
=> x=28:2
Vậy x=14.
\(2^7-3.\left(x+4\right)=23\)
=> 128-3.(x+4)=23
=> 3.(x+4)=128-23
=> 3.(x+4)=105
=> x+4=105:3
=> x+4=35
=> x=35-4
Vậy x=31.
\(2015^x.5^3=125\)
=> 2015x.53=53
=> 2015x=53:53
=> 2015x=1
=> 2015x=20150
Vậy x=0.
a)5x+1=125
=>5x+1=53
=>x+1=3
=>x=2
vậy x=2
b)42x+1=64
=>42x+1=43
=>2x+1=3
=>x=1
vậy x =1
e)=>43x+2017=42020-3
=>3x+2017=2017
=>x=0
vậy x=0
f)=>2x+2x x 23=144
=>2x x (1+23)=144
=>2x x 9=144
=>2x=16
=>2x=24
=>x=4
vậy x=4
\(2^x=32=>x=5\)
\(2^{x+1}=32=>x+1=5=>x=4\)
\(x^3=125=>x=5\)
\(\left(x+1\right)^3=125=>x+1=5=>x=4\)
3. x3 = 125 => x = 5
4. (x + 1)3 = 125
(x + 1)3 = 53
=> x + 1 = 5
=> x = 4
t i c k nhé!! 45457474678789886973463125135153152454654657657868768
a. \(8^{x-3}.8^3=2^5.4^5\)
\(\Rightarrow8^{x-3+3}=32.1024\)
\(\Rightarrow8^{x-3+3}=32768\)
\(\Rightarrow8^{x-3+3}=8^5\)
\(\Rightarrow x-3+3=5\)
\(\Rightarrow x=5+3-3\)
\(\Rightarrow x=5\)
Vậy...
b. \(5^{3.x-2}.125=5^4\)
\(\Rightarrow5^{3x-2}.5^3=5^4\)
\(\Rightarrow5^{3x-2}=5^4:5^3=5^1\)
\(\Rightarrow3x-2=1\)
\(\Rightarrow3x=1+2=3\)
\(\Rightarrow x=3:3=1\)
Vậy...
8x-3.83=25.45
(23)x-3.(23)3=25.(22)5
23(x-3).29=25.210
23x-3.3.29=215
23x-9=215:29
23x-9=24
=>3x-9=4
3x=4+9
3x=15
x=15:3
x=5
\(a,4^{2x-6}=1\)\(\Leftrightarrow2x-6=0\Leftrightarrow2x=6\Rightarrow x=3\)
\(b,2^{2x-1}=16\Rightarrow2^{2x-1}=2^4\)
\(\Rightarrow2x-1=4\Rightarrow2x=5\Rightarrow x=\frac{5}{2}\)
\(c,5< 5^x< 125\Rightarrow5^1< 5^x< 5^3\)\(\Rightarrow1< x< 3\)
\(d,5^{x+1}=125\Rightarrow5^{x+1}=5^3\Rightarrow x+1=3\Rightarrow x=2\)
\(a,4^{2x-6}=1\)
\(4^{2x-6}=4^0\)
\(\Rightarrow2x-6=0\)
\(\Rightarrow2x=6\Leftrightarrow x=3\)
\(b,2^{x-1}=16\)
\(2^{x-1}=2^4\)
\(\Rightarrow x-1=4\)
\(\Rightarrow x=5\)
\(125-\left(x+48\right)=10^2\)
\(\Leftrightarrow125-x-48=100\)
\(\Leftrightarrow77-x=100\)
\(\Leftrightarrow x=77-100\)
\(\Leftrightarrow x=-23\)
\(120-x:4=3^4:3^{11}\)
\(\Leftrightarrow120-x:4=3^{-7}\)
\(\Leftrightarrow120-x;4=\frac{1}{3^7}\)
\(\Leftrightarrow120-x:4=\frac{1}{2187}\)
\(\Leftrightarrow x:4=120-\frac{1}{2187}=\text{119.999542752629}\)
\(\Rightarrow x=\text{119.999542752629}.4=\text{479.998171}\)
125-(x+48)=102
=>125-(x+48)=100
=>x+48=125-100
=>x+48=25
=>x=25-48
=>x=-23
120-x:4=34:311
=>120-x:4=1/2187
=>x:4=120-1/2187
=>x:4=262439/2187
=>x=232439/2137x4
=>x=929756/2187
125 - ( x + 48 ) = 102
125 - ( x + 48 ) = 100
x + 48 = 125 - 100
x + 48 = 25
x = 25 - 48
x = -23
\(4\cdot2^x-3=125\)
\(\Rightarrow4\cdot2^x=125+3\)
\(\Rightarrow4\cdot2^x=128\)
\(\Rightarrow2^x=128:4\)
\(\Rightarrow2^x=32\)
\(\Rightarrow x=5\)
\(\Leftrightarrow4.2^x=125+3=128\)
\(\Leftrightarrow2^x=128:4=32\)
\(\Rightarrow x=5\)